2019
DOI: 10.1002/celc.201801610
|View full text |Cite
|
Sign up to set email alerts
|

Sphere‐and‐Flake‐Structured Cu, N Co‐Doped Carbon Catalyst Designed by a Template‐Free Method for Robust Oxygen Reduction Reaction

Abstract: The suitable structural design of carbon catalysts is a straightforward strategy to achieve a superior electrocatalytic activity for the oxygen reduction reaction. Herein, we firstly design a three-dimensional sphere-and-flake-structured Cu, N co-doped carbon catalyst, via a template-free method, for robust oxygen reduction reaction. The nanostructure is composed of graphene-like nanosheets and carbon nanospheres with abundant mesopores, which can expose numerous active sites. Cu 2 + and the copolymer of PANI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…When the local electronic structure of the hybrid is affected by the generation of lattice defects, the optimal S substitution tends to induce additional catalytic active sites, thereby improving the kinetics of ORR and OER. ,,, In addition, the analysis of the above XPS can be used as proof of the appropriate covalent binding of sulfur powder with C 3 N 4 and CNTs to form N and S codoped carbon skeleton. The six fitting peaks of the spectrum of Co 2p (Figure d) in (Cu, Co) 3 OS 3 @CNT-C 3 N 4 and CoS 2 @CNT-C 3 N 4 are Co 2+ (780.6/797.5 eV), Co 3+ (779.1/794.3 eV), and two vibrational satellites (784.0/803.6 eV). ,, Comparing the peak intensity of these two samples, it can be found that the addition of Cu makes the Co 3+ to increase sharply and the Co 2+ to decrease correspondingly. It is worth mentioning that Co 3+ is in a highly active spin state and thus has the ability to attract and contribute electrons, which is beneficial to the improvement of ORR performance. , Additionally, the six matched peaks of the Cu 2p spectrum (Figure e) in (Cu, Co) 3 OS 3 @CNT-C 3 N 4 and CuS@CNT-C 3 N 4 are Cu + (932.5/952.3 eV), Cu 2+ (934.5/955.3 eV), and two vibrational satellites (945.1/963.3 eV). , For the spectrum of S 2p in (Cu, Co) 3 OS 3 @CNT-C 3 N 4 , CoS 2 @CNT-C 3 N 4 , and CuS@CNT-C 3 N 4 (Figure f), the binding energies at 162.3, 162.9, 164.1, 169.1, and 170.2 eV correspond to Cu–S, S 2p 3/2 , S 2p 1/2 , and the surface oxidation of metal sulfides. ,, By comparing the S 2p spectrum of the three catalysts, it is found that (i) the peak intensity of the two pairs of S 2p 3/2 –2p 1/2 was improved for (Cu, Co) 3 OS 3 @CNT-C 3 N 4 and (ii) the substitution of Cu leads to the sharp decline of the peak intensity of two vibrational satellites, revealing that a lot of S substitution were doped into the lattice and inhibited the oxidation of the samples.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…When the local electronic structure of the hybrid is affected by the generation of lattice defects, the optimal S substitution tends to induce additional catalytic active sites, thereby improving the kinetics of ORR and OER. ,,, In addition, the analysis of the above XPS can be used as proof of the appropriate covalent binding of sulfur powder with C 3 N 4 and CNTs to form N and S codoped carbon skeleton. The six fitting peaks of the spectrum of Co 2p (Figure d) in (Cu, Co) 3 OS 3 @CNT-C 3 N 4 and CoS 2 @CNT-C 3 N 4 are Co 2+ (780.6/797.5 eV), Co 3+ (779.1/794.3 eV), and two vibrational satellites (784.0/803.6 eV). ,, Comparing the peak intensity of these two samples, it can be found that the addition of Cu makes the Co 3+ to increase sharply and the Co 2+ to decrease correspondingly. It is worth mentioning that Co 3+ is in a highly active spin state and thus has the ability to attract and contribute electrons, which is beneficial to the improvement of ORR performance. , Additionally, the six matched peaks of the Cu 2p spectrum (Figure e) in (Cu, Co) 3 OS 3 @CNT-C 3 N 4 and CuS@CNT-C 3 N 4 are Cu + (932.5/952.3 eV), Cu 2+ (934.5/955.3 eV), and two vibrational satellites (945.1/963.3 eV). , For the spectrum of S 2p in (Cu, Co) 3 OS 3 @CNT-C 3 N 4 , CoS 2 @CNT-C 3 N 4 , and CuS@CNT-C 3 N 4 (Figure f), the binding energies at 162.3, 162.9, 164.1, 169.1, and 170.2 eV correspond to Cu–S, S 2p 3/2 , S 2p 1/2 , and the surface oxidation of metal sulfides. ,, By comparing the S 2p spectrum of the three catalysts, it is found that (i) the peak intensity of the two pairs of S 2p 3/2 –2p 1/2 was improved for (Cu, Co) 3 OS 3 @CNT-C 3 N 4 and (ii) the substitution of Cu leads to the sharp decline of the peak intensity of two vibrational satellites, revealing that a lot of S substitution were doped into the lattice and inhibited the oxidation of the samples.…”
Section: Resultsmentioning
confidence: 93%
“…The six fitting peaks of the spectrum of Co 2p (Figure 2d) in (Cu, Co) 3 OS 3 @CNT-C 3 N 4 and CoS 2 @CNT-C 3 N 4 are Co 2+ (780.6/797.5 eV), Co 3+ (779.1/794.3 eV), and two vibrational satellites (784.0/803.6 eV). 28,54,55 Comparing the peak intensity of these two samples, it can be found that the addition of Cu makes the Co 3+ to increase sharply and the Co 2+ to decrease correspondingly. It is worth mentioning that Co 3+ is in a highly active spin state and thus has the ability to attract and contribute electrons, which is beneficial to the improvement of ORR performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The comparison between the control material PANI-TS-TC ( Figure 5 a1,a2) and those containing the metallic species PANI-Ni-TS-TC ( Figure 5 b1,b2) and PANI-Co-TS-TC ( Figure 5 c1,c2) shows the presence of micro-structured particles of different shape and size. For polyaniline-based materials, it is known that the thermal treatment under an inert atmosphere of argon or nitrogen at 600–1200 °C will trigger the rearrangement of the different atoms to create new bonds of carbon–carbon (C-C, C=C, C-H) and carbon–nitrogen (pyridinic-N, pyrrolic-N, and graphitic-N) in a nanostructured network that has different levels of electrical conductivity, number of active sites and electrocatalytic kinetics [ 18 , 20 , 54 , 55 , 56 , 57 , 58 ]. In order to obtain a qualitative analysis of the nature of the structures formed with metallic species, in-depth analysis was conducted by EDX.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the metal content of about 30 wt % is in agreement with the theoretical expectation by considering the mineralization yield of our protocol. It is known that during the calcination, the rearrangement of the different atoms from the starting materials produces the bonds such as carbon-carbon (C-C, C=C, C-H) and carbon-nitrogen (pyridinic-N, pyrrolic-N, and graphitic-N) within a porous-like structure that contribute to the performance by the electrical conductivity, the electrocatalytic kinetics and the high number of active sites [ 42 , 49 , 50 , 51 , 52 , 53 , 54 ]. Our previous and extensive study (SEM, EDX, TGA-DSC, XPS, BET, XRD, etc.)…”
Section: Resultsmentioning
confidence: 99%